PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG, CEO TENURE, DAN FIRM AGE TERHADAP NILAI PERUSAHAAN : THE EFFECT OF DIVIDEND POLICY, DEBT POLICY, CEO TENURE, AND FIRM AGE ON FIRM VALUE - Amanda, Serly; Zirman, Zirman; Hariyani, Eka (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
Competition in the business world is increasing, this encourages every company to improve its performance and quality in order to survive in competition in the business world to get the best value for the company. This research aims to examine and analyze the effect of dividend policy, debt policy, CEO tenure, and firm age on firm value in Kompas100 index companies listed on the Indonesia Stock Exchange in 2018-2022. This research method is a quantitative research method. The population in this research is the KOMPAS 100 index companies which are consistently listed on the Indonesia Stock Exchange (BEI) in 2018-2022, totaling 52 companies. The sample selection in this research used the purposive sampling method. The samples selected in this research was 35 companies selected based on predetermined criteria with a period of 5 years so that a total of 175 data were obtained. The data analysis method used in this research uses WarpPLS 7.0. The research results showed that dividend policy, debt policy, and CEO tenure has an effect on firm value. Meanwhile, firm age has no effect on firm value. These findings suggest that companies seeking to enhance their value should focus on optimizing dividend and debt policies and consider the role of CEO tenure in strategic planning. These results also provide insights for stakeholders and policymakers in formulating strategies to support company growth and stability in a competitive market.